The impact of continuous use intention of cooperative members on new agricultural technologies - Jia, Fang; Zhang, Runhan; Li, Jiajun (Frontiers in Psychology, 2023)
The widespread application of new agricultural technologies promotes the increase of agricultural production and income and the optimization and adjustment of industrial structure. However, there are problems such as low promotion efficiency, insufficient transformation of achievements and mismatch of supply and demand in the process of promotion. Based on the research context of farmers' cooperatives in China, this study explores the factors influencing cooperative members' continuous use intention toward new agricultural technologies and builds a research structure based on the Unified Theory of Acceptance and Use of Technology (UTAUT) model, which includes performance expectations, effort expectations, cooperative Social Impact, and policy support. A total of 401 valid questionnaires were collected and the data were analyzed in three stages with descriptive statistics, measurement validation model, and structural equation model by using a survey questionnaire and inviting members of farmer cooperatives within China to participate in an online survey through a web-based electronic questionnaire. The results of the study found that policy support plays a dominant role in farmers' cooperative members' intention to use new agricultural technologies consistently, and cooperative Social Impact plays a facilitating role; while factors such as performance expectation and effort expectation also have a significant positive effect on the intention to use consistently.